The challenges and the coping strategies of hospitality educators to pursue their part-time study for continuous professional development / Faezanuurfarhha Md Yusof - Md Yusof, Faezanuurfarhha (2023)
A rapid evolution of education demands educators to constantly enhance and develop their competencies in teaching field. Engaging educators in ongoing professional development is a transformative effort to enhance learning and teaching process. Pursuing continuing education and certification are very applicable to be implemented in educators' professional development. By continuing study, the educators can continuously improve and update their knowledge and skills in their area of expertise, to find out new teaching methods, current trends and best practices in their field. The demands of educators' work responsibilities make it impossible for them to study in full-time mode. Part-time study provide opportunity to the educators to combine their professional role of being a student and the employee at the same time. However, unlike the other students who can fully concentrate on their study, where the educators are also required to perform their existing work commitments and other social obligations. These situations are likely to present a number of challenges to the educators as part time learners. Therefore, this research was conducted to explore the challenges faced by hospitality educators as part-time learners and the coping strategies used by them in integrating their part-time study with work and social obligations. Coping strategies refer to one's ability and strategies used to cope with stressful situations. Ten educators from two private hospitality institutions in Johor Bahru, Johor, Malaysia were involved in semi-structured interview sessions, where their organization supports and encourages continuous professional development (CPD) in their professions. Seven major themes were derived from research findings by using thematic analysis. Three themes derived on the challenges faced by educators as part time learners including: (1) conflicting commitments, (2) difficulties in managing time and (3) stress. Meanwhile, four more themes derived related to the coping strategies used by educators to integrate their part time study with work and social obligations including: (1) social support, (2) negotiation arrangement, (3) relaxation techniques and (4) religion spiritual approach. The study findings suggested that those who adopt suitable coping mechanisms can cope with the challenges they faced, able to manage their commitments well and more likely to complete their study successfully. There is a role of academics and higher institution administration in providing better support systems in assisting part-time students to adapt with their study. To the organization, continuous learning can contribute to new ideas and knowledge, a forward-thinking innovation culture in the workplace and positive attitude towards work performance as it is necessary for every profession to increase the level of professionalism